In memoriam - Nigel Groom - Rex Smith, G. (Proceedings of the Seminar for Arabian Studies, 2015)
Nigel Groom, OBE, Arabist, historian, spy-catcher, and writer on perfume, died on 5 March 2014 aged 89. He was born on 26 April 1924 and grew up in Devon, where his father was a country rector.